PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN TAMU DI MANADO QUALITY HOTEL - Wijanarko, Sony; Lieke, Johny; Makakombo, Esterlita (Jurnal Hospitaliti, 2023)
This study aims to find out how the Effect of Service Quality and Facilities on Guest Satisfaction at Manado Quality Hotel. The research method used is quantitative method, with multiple linear regression data analysis techniques. The population in this study were hotel guests, with a sample of 30 guests at Manado Quality Hotel. The results of the study proved that the Quality of Service and Facilities had a positive and significant effect on Guest Satisfaction with a regression coefficient value of 3,225 and a significance of . This shows that the higher the Quality of Employee Service, the higher the Guest Satisfaction. The facility has a positive and significant effect on Guest Satisfaction with a regression coefficient value of 8.738 and a significance of 0.000. This shows that the better the facilities available at the hotel, the better the Guest Satisfaction will be. Quality of Service and Facilities has a significant influence on Guest Satisfaction with an F-count value of 161,471 and a significance of 0.000. This shows that the better the Quality of Service and Facilities, the more Guest Satisfaction will increase. The conclusion of this study is that the Quality of Service and Facilities has a significant influence on Guest Satisfaction at Manado Quality Hotel. The advice given is that Manado Quality Hotel must provide good service in accordance with applicable Standard Operating Procedures and Complete some of the Facilities needed by Guests to increase guest satisfaction during the stay.